Effects of 3, 3', 5‐triiodothyronine on microglial functions. Issue 5 (30th January 2015) - Mori, Yuki; Tomonaga, Daichi; Kalashnikova, Anastasia; Furuya, Fumihiko; Akimoto, Nozomi; Ifuku, Masataka; Okuno, Yuko; Beppu, Kaoru; Fujita, Kyota; Katafuchi, Toshihiko; Shimura, Hiroki; Churilov, Leonid P.; et al.
Abstract : l ‐tri‐iodothyronine (3, 3', 5–triiodothyronine; T3) is an active form of the thyroid hormone (TH) essential for the development and function of the CNS. Though nongenomic effect of TH, its plasma membrane–bound receptor, and its signaling has been identified, precise function in each cell type of the CNS remained to be investigated. Clearance of cell debris and apoptotic cells by microglia phagocytosis is a critical step for the restoration of damaged neuron‐glia networks. Here we report nongenomic effects of T3 on microglial functions. Exposure to T3 increased migration, membrane ruffling and phagocytosis of primary cultured mouse microglia. Injection of T3 together with stab wound attracted more microglia to the lesion site in vivo . Blocking TH transporters and receptors (TRs) or TRα‐knock‐out (KO) suppressed T3‐induced microglial migration and morphological change. The T3‐induced microglial migration or membrane ruffling was attenuated by inhibiting Gi /o ‐protein as well as NO synthase, and subsequent signaling such as phosphoinositide 3‐kinase (PI3K), mitogen‐activated protein kinase (MAPK)/extracellular signal‐regulated kinase (ERK). Inhibitors for Na + /K + ‐ATPase, reverse mode of Na + /Ca 2+ exchanger (NCX), and small‐conductance Ca 2+ ‐dependent K + (SK) channel also attenuated microglial migration or phagocytosis. Interestingly, T3‐induced microglial migration, but not phagocytosis, was dependent on GABAA and GABAB receptors, though GABA itself did not affect migratory aptitude. Our results demonstrate that T3 modulates multiple functional responses of microglia via multiple complex mechanisms, which may contribute to physiological and/or pathophysiological functions of the CNS. GLIA 2015:63:906–920 Main Points: Nongenomic effects of thyroid hormone were investigated in cultured mouse microglia. Thyroid hormone increased motility, chemotaxis and phagocytosis of microglia via complex signaling and attracts more microglia to lesion site in vivo. T3 is an important signaling factor that affects microglial functions and consequently may affect development and maintenance of the brain.